Mindfulness or Sati?: An Anthropological Comparison of an Increasingly Global Concept - Cassaniti, Julia (Journal of global buddhism, 2021)
This article offers a comparison of some of the meanings of mindfulness in secular US settings and Theravāda Buddhist communities of South and Southeast Asia. Based on ethnographic data gathered from over 700 psychiatrists, Buddhist monks, lay practitioners, and others in Thailand, Myanmar, Sri Lanka, and the United States, the article suggests some key mental associations in mindfulness and sati that converge and diverge across different cultural contexts. I call these the “TAPES” of the mind: relationships that mindfulness and sati have to particular conceptions of Temporality, Affect, Power, Ethics, and Selfhood. The article examines each of these “TAPES” and their expressions in the field in turn, from the temporal significance of “remembering the present” to the effects of supernatural and political potencies, to the morality of practice and the ontological status of the self. I argue that when the two terms are used interchangeably some meanings of these associations become privileged, while others are effectively erased. I conclude with a discussion of the problems of hegemonizing discourses about mindfulness, and the implications of the findings for global health and Buddhist studies.